Developing English Proficiency through Qualitative Study of “English With Lucy” YouTube Channel - Simbolon, Sulistina Ratulani; Ismahani, Siti (Universitas Negeri Semarang, 2024)
In the era of globalization, utilizing online platforms for language learning has become increasingly prevalent. This study explores the use of the YouTube channel